Pengembangan Rencana Pelaksanaan Pembelajaran (RPP) Menggunakan Model Snowball Throwing Pada Pembelajaran Tematik di Kelas V Sekolah Dasar (SD) Negeri Kota Bengkulu - Aldi Hamzah; Daimun Hambali; Resnani Resnani (JURIDIKDAS, 2020)
This study aims to describe the results and process of developing lesson plans using the Snowball Throwing model in grade V Elementary School (SD). By designing a product in the form of RPP in thematic learning using the Snowball Throwing model, RPP development is carried out in several stages, namely: defining (defining), designing, developing (development) after successfully developing RPP then RRP validation by experts in two stages. In stage 1, the input of suggestions and comments from experts is used to revise the RPP, obtained an assessment of 83.65 with a good category, and in stage 2 an assessment of 88.45 is obtained with the very good category. Meanwhile, the teacher's assessment results obtained an average of 91.25 which is in the very good category. The conclusion of this study is to produce a thematic lesson plan development product using the Snowball Throwing model in grade V elementary schools.